La coherencia de la disciplina del dumping con la disciplina de la libre competencia en el Perú: el caso de dumping de la República Popular de China - Cannock, Geoffrey (2020)
The Peruvian competition authority Indecopi simultaneously upholds the duties of ensuring a free market as well as protecting it from distortions caused by dumping practices. Such incoherence is evident, since both disciplines are based upon opposite principles: one favors free trade, while the other tends toward protectionism.In this article, the authors explore Indecopi’s dumping policy and how it can collide with the maintenance of a free market. To achieve this, they analyze the legal basis of the WTO’s Antidumping Agreement in Peru, they explain the theories and effects of dumping practices and, at last, they critically analyze the antidumping measures taken by Indecopi against Chinese footwear. The authors close the article by recommending ways in which Indecopi can improve its performance in these types of matters.